Theoretical study on the charge transport properties of three series of dicyanomethylene quinoidal thiophene derivatives. Issue 6 (23rd January 2019) - Lin, Pan-Pan; Zhang, Shou-Feng; Zhang, Ning-Xi; Fan, Jian-Xun; Ji, Li-Fei; Guo, Jing-Fu; Ren, Ai-Min
Abstract : The effects of different connection modes on the electronic structure, electron injection ability, air stability and charge transport properties were researched. Further weak interaction was investigated to analyze the influence of terminal group and the different backbone on molecular packing. Abstract : It is very important to analyse the most advantageous connection style for quinoidal thiophene derivatives, which are used in n-type organic semiconductor transport materials. In the present work, the charge transport properties of three series of quinoidal thiophene derivatives, oligothiophene (seriesA ), thienothiophene (seriesB ) and benzothiophene (seriesC ), are systematically investigated by employing full quantum charge transfer theory combined with kinetic Monte-Carlo simulation. The single crystal structures of the molecules we had constructed were predicted using the USPEX program combined with density functional theory (DFT) and considering the dispersion corrected. Our theoretical results expounded how the different connection styles, including oligo-, thieno-, and benzo-thiophene in the quinoidal thiophenes derivatives, effectively tune their electronic structures, and revealed how their intermolecular interactions affect the molecular packing patterns and hence their charge transport properties by symmetry-adapted perturbation theory (SAPT). In the meantime we also elucidated the role of end-cyano groups in noncovalent interactions. Furthermore, it is clarified that quinoidal thiophene derivatives show excellent carrier transport properties due to their optimal molecular stacking motifs and larger electronic couplings besides their low energy gap. In addition, our theoretical results demonstrate that quinoidal oligothiophene derivatives ( n = 3–5) with more thiophene rings will have ambipolar transport properties, so quinoidal thienothiophene and benzothiophene derivatives should be promising alternatives as n-type OSCs. When we focused only on the electronic transport properties in the three series of molecules, quinoidal benzothiophene derivatives were slightly better than quinoidal oligothiophene or thienothiophene derivatives.